Growth Response of Melati Plant Plant (Jasminum Sambac L.) Against Types of Media Plants and Types of Growing Agents - Yuliatul Muslimah; Sumeinika Fitria Lizmah; Nur Fayanti (Budapest International Research and Critics University, 2020)
Propagation of jasmine plants by cuttings often experience obstacles, especially to grow roots. Proper planting media and application of growth regulators (PGR) have an important role in the growth and development of plant cuttings roots. The purpose of this study was to determine the effect of planting media types and PGR on the growth of jasmine cuttings. This research was conducted in the experimental garden of the Faculty of Agriculture, Teuku Umar University, in March - May 2019. This study used a completely randomized design (CRD) with a factorial pattern of 3x3 with three replications. The treatment factors studied were (1) the type of planting media consisted of 3 levels namely alluvial soil, sand and husk charcoal, and (2) the type of growth regulator (ZPT) consisted of 3 levels namely control (without zpt), chemical (growtone) and organic (shallot extract). F test results on the analysis of variance showed that the planting medium had a very significant effect on the number of shoots 35 and 45 HST, number of leaves 15, 35 and 45 HST number of roots, root length, percentage of live cuttings. But the planting media had no significant effect on the number of shoots of 15 DAP. Growth regulator substances have a very significant effect on the number of shoots 35 HST, number of leaves 15, 35 and 45 HST, number of roots and root length. Significantly affect the number of shoots 45 HST and percentage of live cuttings, but no significant effect on the number of shoots 15 HST. This shows that the difference in growth of jasmine plant cuttings due to different planting media does not depend on growth regulators, and vice versa.